1993
DOI: 10.1063/1.464497
|View full text |Cite
|
Sign up to set email alerts
|

Elastic properties of water under negative pressures

Abstract: Using Brillouin scattering we have investigated the elastic properties of water under negative pressures. The samples were H2O liquid–vapor inclusions in α-quartz which could be heated to their homogenization temperatures (in the range 120–370 °C); on cooling, negative pressures as high as 1000 bars were reached before a vapor bubble nucleated. The velocity of sound results obtained from our Brillouin experiments indicate that nucleation occurs long before reaching the mechanical instability region where the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
78
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(83 citation statements)
references
References 17 publications
5
78
0
Order By: Relevance
“…[57][58][59][60][61][62][63][64] Water is in many ways an ideal liquid for such studies, in that it has an extremely high tensile strength for a liquid due to the high degree of hydrogen bonding. However, heterogeneous nucleation generally prevents water from being stretched to its intrinsic tensile strength.…”
Section: T 1 T Fill T 2 > T Fill T 3 < T Fill T Break < Tmentioning
confidence: 99%
“…[57][58][59][60][61][62][63][64] Water is in many ways an ideal liquid for such studies, in that it has an extremely high tensile strength for a liquid due to the high degree of hydrogen bonding. However, heterogeneous nucleation generally prevents water from being stretched to its intrinsic tensile strength.…”
Section: T 1 T Fill T 2 > T Fill T 3 < T Fill T Break < Tmentioning
confidence: 99%
“…The estimate was based on an extrapolated EoS, using the density obtained from the temperature at which the bubble in the Berthelot tube disappears upon heating, and assuming that the inclusion volume does not change with temperature. A Brillouin scattering study [39] showed that this assumption could be wrong in very thin inclusions, but that it seemed correct in more rounded ones.…”
Section: The Enigma Of the Cavitation Pressure Of Watermentioning
confidence: 99%
“…Berthelot tube method (7,(18)(19)(20). A closed, rigid container with a fixed amount of water is heated until the last vapor bubble disappears at T h .…”
Section: Fig 2 Experiments On Metastable Liquid Water (A)mentioning
confidence: 99%